The web unveiled: A rare case of bilateral carotid web presenting as acute ischemic stroke - Madhusudhan , Jaladhi; Nevil, Shaun; Charles, S Anton; Umesh, G; Mondal, Sofia; Chaitra, C S (Indian Journal of Case Reports, 2026)
Carotid web (CaW) is a focal intimal variant of fibromuscular dysplasia (FMD) that has emerged as an important cause of cryptogenic stroke. Although most commonly reported as unilateral presentation, bilateral CaWs are exceptionally rare and remain poorly documented in existing literature. We report the case of a 58-year-old male presenting with acute-onset right-sided hemiparesis following a transient loss of consciousness. Vascular evaluation using carotid Doppler and magnetic resonance angiography demonstrated bilateral CaW involving the right common carotid artery and left internal carotid artery, causing moderate luminal stenosis. This case highlights the diagnostic challenges associated with a CaW, as the lesion is often subtle and may be overlooked on routine ultrasonography, leading to diagnostic delay. Early recognition and the use of appropriate vascular imaging modalities are crucial for accurate etiological assessment and optimal management of ischemic stroke.